Estrus synchronization and ovarian hyper‐stimulation treatments have negligible effects on cumulus oocyte complex gene expression whereas induction of ovulation causes major expression changes. Issue 2 (13th February 2013) - Agca, Cansu; Yakan, Akin; Agca, Yuksel
Abstract The effects of exogenous hormones, used for estrus synchronization and ovarian hyper stimulation, on cumulus oocyte complexes (COCs) gene expression in sexually mature rats were determined using microarrays. Gene expression in COCs collected from GnRH (Gtrt), GnRH + eCG (G + Etrt), and GnRH + eCG + hCG (G + E + Htrt) treatments were compared to COCs from naturally cycling (NC) rats before the preovulatory luteninizing hormone surge. There was no significant difference in gene expression among NC, Gtrt, and G + Etrt; however, over 2, 600 genes were significantly different between NC and G + E + Htrt (P < 0.05). Genes upregulated in G + E + Htrt encode for: proteins that are involved in prostaglandin synthesis (Ptgs2, Pla2g4a, and Runx1) and cholesterol biosynthesis (Hmgcr, Sc4mol, and Dhcr24); receptors that allow cholesterol uptake (Ldlr and Scarb1), regulate progesterone synthesis (Star), and inactivate estrogen (Sult1e1); and downstream effectors of LH signal (Pgr, Cebpb, Creb3l1, Areg, Ereg, and Adamts1). Conversely, G + E + Htrt downregulated genes encoding proteins involved in: DNA replication and cell cycle progression (Ccne2, Orc5l, Rad50, and Mcm6); reproductive developmental process; and granulosa cell expansion (Gdf9, Bmp15, Amh, Amhr2, Bmpr1b, Tgfb2, Foxl2, Pde3a, Esr2, Fshr, Ybx2, Ccnd2, Ccnb1ip1, and Zp3); maternal effect genes required for embryo development (Zar1, Npm2, Nlrp5, Dnmt1, H1foo, and Zfp57); amino acid degradation; and ketogenesis (Hmgcs2, and Cpt1b). These results from the rat show that hormones used for estrus synchronization (Gtrt) and ovarian hyper stimulation (G + Etrt) had minimal effects on gene expression, whereas induction of ovulation (G + E + Htrt) caused major changes in gene expression of rat COCs. This study provides comprehensive information about regulated genes during late follicle development and ovulation induction. Mol. Reprod. Dev. © 2013 Wiley Periodicals, Inc.